Sol-gel-driven combustion wave for scalable transformation of Mn(NO3)2 precursors into MnO2-X/MWCNT supercapacitor electrodes capable of electrochemical activation. (November 2019) - Shin, Dongjoon; Hwang, Hayoung; Yeo, Taehan; Park, Seonghyun; Kim, Taewon; Lee, Jaeho; Choi, Wonjoon
Abstract: Hybrids of carbon-based materials and metals/metal oxides have emerged as promising candidates for electrochemical electrodes. While porous and inter-connected networks are necessary for a high specific area and an outstanding electrochemical resistance, the fabrication of rationally designed hybrids requires complex procedures. Herein, we report sol-gel-driven combustion waves (CWs) for one-step transformation from Mn(NO3 )2 /multi-walled carbon nanotube (MWCNT) into MnO2-X /MWCNT hybrids capable of electrochemical activation. A solidified Mn(NO3 )2 /MWCNT/nitrocellulose (NC) mixture was prepared by applying drop-casting/drying processes to a precursor solution. The sol-gel-driven CWs, induced through the exothermic reaction of NC, conducted a rapid thermochemical transformation into MnO2-X /MWCNT hybrids. Electrochemical activation using cyclic voltammetry methods resulted in the anodizing and oxidizing of MnO2-X /MWCNT hybrids, thereby presenting porous and inter-connected MnO2 /MWCNT electrodes consisting of plate-like MnO2 structures and embedded MWCNTs, as well as the increasing capacitance by 42.5%. Owing to the extended surface area of the porous MnO2 having the conductive networks of entangled MWCNTs among plate-like structures, MnO2 /MWCNT supercapacitor electrodes exhibited a highly enhanced specific capacitance (∼259.6 F/g) and an outstanding long-term capacitance retention over 10, 000 charge-discharge cycles (∼91% at 100 mV/s). The fabrication strategy using sol-gel-driven CWs enables a facile, new synthesis method for versatile hybrids of carbon-based materials and metals/metal oxides. Graphical abstract: Image 1